The synthesis of novel 4-(3,4-dimethoxyphenyl)chromenone-crown ethers and their cation binding, as determined using fluorescence spectra - (:unkn) unknown (My University, 2009)
o-Dihydroxy-4-(3,4-dimethoxyphenyl)-chromenones (coumarins; 3a,b) were synthesised from 1,2,3-trihydroxy- or 1,2,4- triacetoxybenzenes through a reaction with ethyl 3-(3,4-dimethoxyphenyl)-3-oxopropanoate in H2SO4 or CF3COOH. The chromenone-crown ethers (4a-f) were prepared from the cyclic condensation of o-dihydroxy-4-(3,4-dimethoxyphenyl)- chromenones (3a,b) with poly(ethylene glycol) ditosylates, in the presence of CH3CN/alkali carbonates. The chromatographically purified original chromenone-crown ethers were identified by 1H NMR, 13C NMR, MALDI-TOF mass spectrometry and elemental analysis. The 1:1 binding constants of Li+, Na+ and K+ with the chromenone-crown ethers were estimated in acetonitrile using fluorescence emission spectroscopy. The complexing-enhanced fluorescence spectra and complexing-enhanced quenching fluorescence spectra, along with the cationic recognition rules of the crown ethers allowed the ion binding powers to be determined. © 2009 Taylor & Francis.
Keywords: Cation binding; Chromenone-crown ether; Coumarin; Fluorescence spectroscopy; Synthesis